Understanding the Pathogenicity of Noncoding Mismatch Repair Gene Promoter Variants in Lynch Syndrome. Issue 5 (18th March 2016) - Liu, Qing; Thompson, Bryony A.; Ward, Robyn L.; Hesson, Luke B.; Sloane, Mathew A.
ABSTRACT: Lynch syndrome is the most common familial cancer condition that mainly predisposes to tumors of the colon and endometrium. Cancer susceptibility is caused by the autosomal dominant inheritance of a loss‐of‐function mutation or epimutation in one of the DNA mismatch repair (MMR) genes. Cancer risk assessment is often possible with nonsynonymous coding region mutations, but in many cases patients present with DNA sequence changes within noncoding regions, including the promoters, of MMR genes. The pathogenic role of promoter variants, and hence clinical significance, is unclear and this hinders the clinical management of carriers. In this review, we provide an overview of the classification of MMR gene variants, outline the laboratory assays and online resources that can be used to assess the causality of promoter variants in Lynch syndrome, and highlight some of the practical challenges of demonstrating the pathogenicity of these variants. In conclusion, we propose a guide that could be integrated into the current InSiGHT classification scheme to help determine if a MMR gene promoter variant is pathogenic.